Abu Mina, Ägypten: Das Pilgerzentrum - Grossmann, Peter (e-Forschungsberichte des DAI, 2023)
Abu Mina is a late antique pilgrimage centre (not a monastery) situated in the Libyan desert, ca. 60 km to the southwest of Alexandria. It developed around the burial place of St. Menas, who, according to the legend, received martyrdom under the Roman emperor Diocletian (284‒305) during the early 4th century. The site contains several large churches, bath buildings, rest houses for pilgrims etc. which are forming the main buildings of an ecclesiastical centre surrounded by a girdle of mostly private villas. The excavations were interrupted for several years. Only in April 2013 permission for field work activities was again granted.